Study the Indian Legislative Action in Protecting the Rights of Victims: Examining the Neglect of Victim's Rights in the Indian Criminal Justice System (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Victim’s compensation and restitution has always been neglected in the Indian criminal justice system. There is not a single legislative act for the compensation and betterment of the crime victims in India. The crime victim has no various rights of criminal justice system. In any crime, the main focus has been always on the accused persons and his rehabilitation but no one gave his attention towards the victim of crime. The status of victim in crime is like as ignored person in the criminal justice system. No one is here to talk about the rights and restitutions of the crime victim. From the starting of twenty century, it had been seen that the position of the crime victim is lesser than the accused in the criminal justice system. In the recent decades, the position of the crime victims has been looked up as ignored person in the criminal justice system by the various countries of the world.